Contribution of formulation and implementation strategy on organizational performance: examining the moderating effect of organizational culture / Yassien Ahmed Housen Masoud - Masoud, Yassien Ahmed Housen (2016)
Formulation and implementation strategy play a major role in organizational performance. The main purpose of this study was to examine the relationship between formulation and implementation strategy on organizational performance and examined the moderating effect of organizational culture on this relationship in Yemen of Ministry of Health. The population of the study was staff at top and middle management level in Yemen Ministry of Health. Data was collected based on self-administered questionnaire from the selected sample. 120 useable samples based on the random sampling were used in the study among staff at top and middle management in the Yemen Ministry of Health. Data in this study was analyzed based on descriptive and inferential statistics using SPSS version 22. The finding showed that there was significant and positive relationship between formulation and implementation strategy with organizational performance. The findings showed that the implementation strategy has contribute more significantly than formulation strategy on organizational performance. The findings also showed that organizational culture has moderated the relationship between formulation and implementation strategy and organizational performance. The study is important from the both theoretical and practical perspective especially for practitioner and scholars to refer. This research will provide the Yemen Ministry of Health and other stakeholders with important data and insights on current state and practice of formulation and implementation strategy by Ministry of Health in Yemen.